Hazard quotient profiles used as a risk assessment tool for PFOS and PFOA serum levels in three distinctive European populations. (January 2015) - Ludwicki, Jan K.; Góralczyk, Katarzyna; Struciński, Paweł; Wojtyniak, Bogdan; Rabczenko, Daniel; Toft, Gunnar; Lindh, Christian H.; Jönsson, Bo A.G.; Lenters, Virissa; Heederik, Dick; Czaja, Katarzyna; Hernik, Agnieszka; et al.
Abstract: Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) blood levels are commonly used as biomarkers of human environmental exposure to these compounds. Many biomonitoring studies indicate 100% detection for PFOS and PFOA thus justifying a concern of possible risk for the most exposed individuals. This study addresses the predictive value of hazard quotients (HQs) calculated on the basis of serum PFOS and PFOA in male and female populations of reproductive age in Greenland, Poland and Ukraine. Overall, 2026 results of PFOS and PFOA serum concentrations (589 males, 1437 females) were obtained from the INUENDO database. HQs were calculated from the actual biomonitoring results and literature-based animal data linking toxicological outcomes and critical PFOS/PFOA serum levels. HQs for serum PFOS were calculated based on Points of Departure (PoD) at 13 μg mL − 1 (cynomolgus monkeys, 183 days, changes in THS and T3 ) and for PFOA at 7.1 μg mL − 1 serum (male rats, 90 days, hepatocellular necrosis, increased liver weight). Uncertainty factors were applied to reflect interspecies differences and human variability. Serum HQs were expressed as a ratio relative to the point of departure for each PFOS and PFOA. Only in the three cases of males in Greenland were there serum PFOS levels showing HQ values exceeding 1, so indicating that such serum levels may be of concern. The mean serum concentration of PFOS was significantly higher in male than in female populations. Despite significant differences between HQ profiles for PFOS and PFOA in donors from Greenland, Poland and Ukraine, the concentrations of these perfluoroalkylated compounds do not indicate a cause for concern, except for the three aforementioned cases from Greenland. This study demonstrates that the HQ approach can help to interpret human biomonitoring data and thus serve as a valuable tool in further risk assessment priority settings and may also be used as a basis for taking decisions in risk management. Highlights: We analysed the hazard quotients (HQs) for serum PFOS and PFOA in Greenland Inuit, Polish and Ukrainian fertile couples HQs for PFOS and PFOA were below value of 1, except of three Inuit males for which the PFOS serum levels may be of concern We observed the differences in exposure patterns to PFOS and PFOA between males and females and between examined populations Our results confirm the usefulness of the HQs concept as an effective method to interpret biomonitoring results